Pengaruh Good Corporate Governance dan Profitabilitas Terhadap Implementasi Environmental, Social, And Governance (ESG) pada Perusahaan Pertambangan - Firly Selfiannisa; Raida Fuadi; Mulia Saputra; Rita Meutia; Linda Linda (LPPM UBP, 2026)
This study attempts to examine the influence of Good Corporate Governance (GCG) and profitability on the implementation of Environmental, Social, and Governance (ESG) in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population includes all mining companies listed on the IDX. Using a purposive sampling technique, 43 companies were sampled, resulting in a total of 129 observations. However, 33 data points were categorized as outliers due to data discrepancies, particularly in the managerial ownership variable. Therefore, the final data set consisted of 96 observations. Data were obtained from company annual reports and sustainability reports, then analyzed using panel data regression with the Fixed Effect Model (FEM) approach through Eviews 12. GCG variables were measured through audit committees, independent commissioners, institutional ownership, and managerial ownership, while profitability was assessed using Return on Assets (ROA). ESG implementation was measured using indicators according to the Global Reporting Initiative (GRI) standards.